Keterampilan Proses Sains Siswa dalam Pembelajaran Berbasis Eksperimen SMP Negeri 1 Gunungsari - Thoriq Alfarishi; Ilham Jayadi Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze students’ science process skills in experiment-based learning at SMP Negeri 1 Gunungsari. Science process skills are fundamental abilities that include observation, classification, data interpretation, prediction, and scientific communication, which are essential in science learning to build conceptual understanding and critical thinking skills. The research method employed was a quantitative descriptive approach with a case study design. The subjects of this study were eighth-grade students who participated in science learning through an experimental approach. The instruments used included an observation sheet of science process skills and student worksheets (LKS) designed to facilitate exploration, experimentation, and reflection. The results of the study indicate that most students showed improvement in the aspects of observation and data interpretation after participating in experiment-based learning. The aspects of scientific communication and prediction also improved, although the enhancement was not evenly distributed among all students. Factors supporting the development of science process skills included students’ active involvement in the experimental process, structured teacher guidance, and the use of relevant tools and materials. This study concludes that experiment-based learning has a significant contribution to the development of students’ science process skills. It is recommended that teachers systematically and continuously integrate experimental approaches into science instruction.